Analisis kemampuan komunikasi matematis peserta didik ditinjau dari perbedaan gender - Bintania, Yolla; Widiati, Indah (Mahesa Research Center, 2024)
Mathematical communication skills are the basic abilities that students must have in learning mathematics. This research aims to analyze students' mathematical communication skills in terms of gender differences. This type of research is qualitative descriptive research. The subjects in this research were class VIII students at MTs Hasanah Pekanbaru consisting of 3 male students and 3 female students with the categories of high, medium and low ability students. The data collection technique in this research is a test technique using a mathematical communication ability test instrument and a non-test technique, namely an interview guide. The data analysis technique is carried out using the stages of data reduction, data presentation, and drawing conclusions. The results of this study showed that in the high category, male subjects met 3 indicators and less than 1 indicator, while female subjects met 4 indicators. Then in the medium category, male subjects meet 3 indicators and do not meet 1 indicator, while female subjects meet 2 indicators and do not meet 2 indicators. Furthermore, in the low category, male subjects did not meet 1 indicator and did not meet 3 other indicators, while female subjects did not meet 3 indicators and did not meet 1 indicator.